Dynamic Changes in the Human Milk Metabolome Over 25 Weeks of Lactation - Poulsen, Katrine Overgaard; Meng, Fanyu; Lanfranchi, Elisa; Young, Jette Feveile; Stanton, Catherine; Ryan, C. Anthony; Kelly, Alan L.; Sundekilde, Ulrik Kraemer (Frontiers in Nutrition, 2022)
Human milk (HM) provides essential nutrition for ensuring optimal infant growth and development postpartum. Metabolomics offers insight into the dynamic composition of HM. Studies have reported impact of lactation stage, maternal genotype and gestational age on HM metabolome. However, the majority of the studies have considered changes within the first month of lactation or sampled with large intervals. This leaves a gap in the knowledge of progressing variation of HM composition beyond the first month of lactation. The objective of this study was to investigate whether the HM metabolome from mothers with term deliveries varies beyond one month of lactation, during the period in which HM is considered fully mature. Human milk samples (n=101) from 59 mothers were collected at week 1-2, week 3-5, week 7-9 and week 20-25 postpartum and analyzed using 1H nuclear magnetic resonance spectroscopy. Several metabolites varied over lactation and exhibited dynamic changes between multiple time-points. Higher levels of human milk oligosaccharides, cis-aconitate, O-phosphocholine, O-acetylcarnitine, gluconate, and citric acid were observed in early lactation, whereas later in lactation, levels of lactose, 3-fucosyllactose, glutamine, glutamate and short- and medium chain fatty acids were increased. Notably, we demonstrate that HM metabolome is dynamic during the period of maturity.